Mechanism of Lys48-linked polyubiquitin chain recognition by the Mud1 UBA domain. - Trempe, J; Brown, N; Lowe, E; Gordon, C; Campbell, I; Noble, M; Endicott, J (2005)
The ubiquitin-pathway associated (UBA) domain is a 40-residue polyubiquitin-binding motif. The Schizosaccharomyces pombe protein Mud1 is an ortholog of the Saccharomyces cerevisiae DNA-damage response protein Ddi1 and binds to K48-linked polyubiquitin through its UBA domain. We have solved the crystal structure of Mud1 UBA at 1.8 angstroms resolution, revealing a canonical three-helical UBA fold. We have probed the interactions of this domain using mutagenesis, surface plasmon resonance, NMR and analytical ultracentrifugation. We show that the ubiquitin-binding surface of Mud1 UBA extends beyond previously recognized motifs and can be functionally dissected into primary and secondary ubiquitin-binding sites. Mutation of Phe330 to alanine, a residue exposed between helices 2 and 3, significantly reduces the affinity of the Mud1 UBA domain for K48-linked polyubiquitin, despite leaving the primary binding surface functionally intact. Moreover, K48-linked diubiquitin binds a single Mud1 UBA domain even in the presence of excess UBA. We therefore propose a mechanism for the recognition of K48-linked polyubiquitin chains by Mud1 in which diubiquitin units are specifically recognized by a single UBA domain.